Tight Junction Proteins and Signaling Pathways in Cancer and Inflammation: A Functional Crosstalk - Bhat, Ajaz A.; Uppada, Srijayaprakash; Achkar, Iman W.; Hashem, Sheema; Yadav, Santosh K.; Shanmugakonar, Muralitharan; Al-Naemi, Hamda A.; Haris, Mohammad; Uddin, Shahab (Frontiers in Physiology, 2019)
The ability of epithelial cells to organize through cell-cell adhesion into a functioning epithelium serves the purpose of a tight protective barrier. Epithelium and endothelium function together by forming an apical junction complex which is made up of tight junctions (TJ), adherens junctions (AJ), and desmosomes. Both adherens junctions and desmosmes impart mechanical adhesion while tight junctions firmly seal the cellular sheets and regulate ion flux that helps in preserving tissue homeostasis. Moreover, tight junctions are involved in maintaining cell polarity and in the establishment of organ-specific apical domains. In addition to these vital functions, tight junction proteins help recruiting signaling proteins involved in the regulation of various important cellular functions including proliferation, differentiation, and migration. Tumor cells frequently exhibit compromised tight junction functions with irregular differentiation and cell polarity, thought to be driving factors for the metastatic phenotype. The tight junction barrier is also compromised in inflammation in response to proinflammatory mediators and plays a major role in disease severity. This review provides a brief introduction about the tight junctions, adherens junctions, structure and function of tight junction proteins. The link between tight junction proteins and key signaling pathways in cell proliferation, transformation, and metastasis is discussed thoroughly. This review also summarizes how tight junction barrier function is compromised under the inflammatory conditions.